Memory training interface for elderly based on mobile app - Batista, A.; Postolache, O.; Mendes, D.; Reis, E.; Nogueira, D. (2022 International Conference and Exposition on Electrical And Power Engineering (EPE), 2022)
Currently, the world population is aging rapidly and one of the characteristics that will accompany this new generation of elderly people is the concept of “aging in place”, which means aging at home. The quality of life of the elderly in their home depends on the maintenance of their cognitive and motor skills and, therefore, the way to encourage them to remain autonomous and reduce institutionalization is by training their memory. To help on solving problems like cognitive decline in elderly population it was developed a memory training mobile application based on life story work. The APP has the contribution of many professionals and was validated with a small group of elderly users. Analysis of the collected data is presented in the work to underline the effectiveness of developed APP on cognitive training.